2018
DOI: 10.1111/jace.15550
|View full text |Cite
|
Sign up to set email alerts
|

Transparent polycrystalline Gd2Hf2O7 ceramics

Abstract: We have successfully developed transparent polycrystalline Gd2Hf2O7 ceramics with high in‐line transparency. A sol–gel process was used to synthesize the Gd2Hf2O7 powder. Simultaneous thermal gravimetric analysis and differential thermal analysis (TGA/DTA) was used to identify the decomposition sequence as a function of temperature for the as‐synthesized sol–gel powders. The calcined powder is single phase and was formed with an estimated average particle size of 120 nm. Crystallization was confirmed by x‐ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…ref49,ref50 In addition, we have found that electronic transition involving ionized oxygen vacancies are responsible for such luminescence properties from our earlier work on Nd 2 Zr 2 O 7 and Gd 2 Zr 2 O 7 pyrochlore. 5,27 The used excitation energy (∼3.37 eV, 332 nm) is less than the band gap (3.42 eV) of GHO, 19,44 so direct transition from the valence band (VB) to the conduction band (CB) does not happen, and there exist certain localized defect states within the band gap of the GHO NPs. Such defects could arise during thermal treatment of the GHO NPs or may be present intrinsically in them.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ref49,ref50 In addition, we have found that electronic transition involving ionized oxygen vacancies are responsible for such luminescence properties from our earlier work on Nd 2 Zr 2 O 7 and Gd 2 Zr 2 O 7 pyrochlore. 5,27 The used excitation energy (∼3.37 eV, 332 nm) is less than the band gap (3.42 eV) of GHO, 19,44 so direct transition from the valence band (VB) to the conduction band (CB) does not happen, and there exist certain localized defect states within the band gap of the GHO NPs. Such defects could arise during thermal treatment of the GHO NPs or may be present intrinsically in them.…”
Section: Results and Discussionmentioning
confidence: 99%
“…18 GHO has a cubic structure as well as high Z eff , making it a potential host lattice for scintillators. 19,20 Moreover, given its high melting point and high structural and thermal stabilities, it can be a potential host for lanthanide ion-doped phosphor. The IRR of GHO is approximately around 1.48 (close to 1.46), 21 so it is expected that the DF and OP phases can coexist in GHO depending on the synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent polycrystalline ceramics have become of interest since Neodymium-doped yttrium aluminum garnet (Nd:YAG) was introduced as a lasing medium for solid state lasers in 1995 [201] and have applications in armors, opto-electrical devices such as solar cells, displays, and circuitries. Compared to single crystals, polycrystalline ceramics are costeffective, easier to produce, exhibit good mechanical, thermal and chemical stability, and shape-control availability [292,293]. However, certain defects such as impurities and porosity inside their microstructure scatter and refract light leading to optical losses, thus limiting wide employment of transparent polycrystalline ceramics [203,294].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Gd 2 Hf 2 O 7 transparent ceramics were prepared from powders synthesized by using a sol-gel process. 74 The powder calcined at 1000 ○ C had an average particle size of 120 nm. The calcined powders were hot-pressed at 1500 ○ C to relative densities of > 95%, whereas fully dense ceramics were obtained after HIP treatment at 1500 ○ C at a pressure of 207 MPa.…”
Section: Hafnatementioning
confidence: 99%